Analysis Of Loan To Deposit Ratio And Non-Performing Loan On Profitability On Profitability PT BPR Dana Nagoya - Susantih Susantih; Hermaya Ompusunggu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The bank aims to obtain income in the form of dividends or benefit from the increase in the price of shares owned. The amount of credit disbursed by a bank will determine the bank's profit, profitability is the net result of a number of policies and decisions of the company. The profitability ratio measures how much the company is capable of making a profit. Profitability is a factor that should receive important attention because it is to be able to carry out the life of a company. This study aims to test the Loan to Deposit Ratio and NonPerforming Loan against profitability. The population in this study was PT BPR Dana Nagoya. The data used in this study is in the form of financial statements of PT BPR Dana Nagoya. In this study, researchers used descriptive statistical data analysis methods, classical assumption tests, normality tests, auto correlation tests, multicorrelarity tests, Heteroskedasticity tests, Hypothesis Tests, Multiple Linear Regression Analysis, and Coefficients of Determination. Based on the results of the t test, it shows that the calculated t value of 2,731 < t table is 1,687.3 and the significance value of t is 0.499 > 0.05, it can be concluded that the Variable Loan to Deposit Ratio (LDR) has a significant positive effect on profitability. Likewise, with the Non Performing Loan (NPL) variable with a calculated t value > t table of 6,151 <1/687 and a significance value of t of 0,000 < 0.05, it can be concluded that the Non Performing Loan (NPL) variable has a negative effect on profitability. Meanwhile, in the F test, the two independent variables jointly influenced profitability by showing a calculated F value of 21,072 > F of table 3.25 and an F significance value of 0.000 < 0.05.